PROSPECTS OF TERTIARY COMPOUNDS (Scientific journal of the Fergana State University, 2024)
This article discusses tertiary alloys and their prospects, solid solutions based on Bi2Te3-Bi2Se3, Bi2Te3-Sb2Te3, which show their best thermoelectric properties operating in a certain temperature range.